(untitled) (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-196-206 The relevance of this study is to optimize decision-making within group strategic sessions, that have become widespread in the educational and creative organizations` management, as well as the need to develop specific management tools and methods in the creative industries, including advertising and communications. To identify the most productive methods for organizing the communication product development process, a field study was developed using experimental methods, observation, comparison, structural-semantic analysis, and integrated assessment based on specified criteria. Comparison of the results of group work in two project sessions, conducted as part of the field study, confirms the efficiency of using creative methods to stimulate the creative process. Comparison of two project sessions, where students worked individually (both with and without creative methods) leads to the conclusion that the use of creative methods does not provide significant advantages and does not improve the quality of the developed projects. This may indicate the ineffectiveness of the focal object method chosen for the experiment. The comparison of the results of individual and group project sessions without the use of creative methods refutes the hypothesis that group work is more effective than individual work in developing communication projects and confirms this if creative methods are used in project sessions. Key words: communication creativity, communication product, creative activity, creative process, methods of creative activity, creative management, research of creative activity, creative personality